The paleontologist : a novel - Dumas, Luke (Atria Paperback, 2023)
"Curator of paleontology Dr. Simon Nealy never expected to return to his Pennsylvania hometown, let alone the Hawthorne Museum of Natural History. He was just a boy when his six-year-old sister, Morgan, was abducted from the museum under his watch, and the guilt has haunted Simon ever since. After a recent break-up and the death of the aunt who raised him, Simon feels drawn back to the place where Morgan vanished, in search of the bones they never found. But from the moment he arrives, things aren't what he expected. The Hawthorne is a crumbling ruin, still closed amid the ongoing pandemic, and plummeting toward financial catastrophe. Worse, Simon begins seeing and hearing things he can't explain. Strange animal sounds. Bloody footprints that no living creature could have left. A prehistoric killer looming in the shadows of the museum. Terrified he's losing his grasp on reality, Simon turns to the handwritten research diaries of his predecessor and uncovers a blood-soaked mystery 150 million years in the making that could be the answer to everything. Are these the ravings of a madman? Or is there something supernatural at play? And what does this have to do with Morgan's disappearance?"--